2023
DOI: 10.1039/d3fo03159d
|View full text |Cite
|
Sign up to set email alerts
|

The ability of supercritical CO2carrot and pumpkin extracts to counteract inflammation and oxidative stress in RAW 264.7 macrophages stimulated with LPS or MDA-MB-231 cell-conditioned media

Luca Frattaruolo,
Miriana Durante,
Maria Stella Cappello
et al.

Abstract: This study describes the effects of extraction method (SFE or CSE) and co-solvent composition (hempseed or  flaxseed) on carrot and pumpkin extracts ability to counteract inflammation and oxidative stress in LPS-stimulated RAW 264.7 macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…NO is one of main mediators of these processes, playing a central role in the modulation of the release of several inflammatory agents [ 55 , 56 ]. Over the years, several reports have demonstrated that natural products from plants, including red raspberries, are able to combat various disorders, such as inflammation [ 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…NO is one of main mediators of these processes, playing a central role in the modulation of the release of several inflammatory agents [ 55 , 56 ]. Over the years, several reports have demonstrated that natural products from plants, including red raspberries, are able to combat various disorders, such as inflammation [ 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%